Vigna comosa Baker Aerial Part’s Extracts Effects on Hyperglycemia and Hepatic Glucose’s Liberation - KOTIN, Lucrèce Mahoutin; AHOUNOU AÏKPE, FIFAMIN JUDITH; AKAKPO, B. Huguette; Assogba, Fidèle; DANSOU, HOUNDJOVI PIERRE; GBENOU, Djimon Joachim (My University, 2021)
Vigna comosa Baker (V. comosa) is a plant used by Beninese Oueme department’s population for the treatment of diabetes without any scientific study showing its effectiveness. The objective of this study is to investigate the effects of the extracts of V. comosaon hyperglycemic rabbits by Oral Glucose Tolerance Test (OGTT) and on hepatic glucose liberation. Phytochemical screening revealed that the plant contains alkaloids, tannins, flavonoids, mucilage, triterpenoids, steroids, reducing compounds, saponins, oses and holosides. Cytotoxity test showed that those extracts were free of toxicity. The extracts showed anti-hyperglycemic activities doses and time depending. The effective doses are 500 mg/kg for the aqueous extract and 1000 mg/kg for the ethanolic extract. The extracts are effective as compared with glibenclamide (reference product). Moreover, the ex vivo test conducted on the liver revealed that V. comosa aqueous extract inhibits the hepatic glucose liberation and 500 mg/mL is the most effective dose. The results of this study account for the plant under consideration of its traditional usage in the treatment of diabetes.
Keywords: Vigna comosa; extracts; phytochemistry; cytotoxicity; hyperglycemia; hepatic glucose.